Chromosome‐level assembly of the Neolamarckia cadamba genome provides insights into the evolution of cadambine biosynthesis. (16th December 2021) - Zhao, Xiaolan; Hu, Xiaodi; OuYang, Kunxi; Yang, Jing; Que, Qingmin; Long, Jianmei; Zhang, Jianxia; Zhang, Tong; Wang, Xue; Gao, Jiayu; Hu, Xinquan; Yang, Shuqi; et al.
SUMMARY: Neolamarckia cadamba (Roxb.), a close relative of Coffea canephora and Ophiorrhiza pumila, is an important traditional medicine in Southeast Asia. Three major glycosidic monoterpenoid indole alkaloids (MIAs), cadambine and its derivatives 3β‐isodihydrocadambine and 3β‐dihydrocadambine, accumulate in the bark and leaves, and exhibit antimalarial, antiproliferative, antioxidant, anticancer and anti‐inflammatory activities. Here, we report a chromosome‐scale N. cadamba genome, with 744.5 Mb assembled into 22 pseudochromosomes with contig N50 and scaffold N50 of 824.14 Kb and 29.20 Mb, respectively. Comparative genomic analysis of N. cadamba with Co .  canephora revealed that N. cadamba underwent a relatively recent whole‐genome duplication (WGD) event after diverging from Co. canephora, which contributed to the evolution of the MIA biosynthetic pathway. We determined the key intermediates of the cadambine biosynthetic pathway and further showed that NcSTR1 catalyzed the synthesis of strictosidine in N. cadamba . A new component, epoxystrictosidine (C27H34N2O10, m / z  547.2285), was identified in the cadambine biosynthetic pathway. Combining genome‐wide association study (GWAS), population analysis, multi‐omics analysis and metabolic gene cluster prediction, this study will shed light on the evolution of MIA biosynthetic pathway genes. This N. cadamba reference sequence will accelerate the understanding of the evolutionary history of specific metabolic pathways and facilitate the development of tools for enhancing bioactive productivity by metabolic engineering in microbes or by molecular breeding in plants. Significance Statement: Coffea canephora, Ophiorrhiza pumila and Neolamarckia cadamba are three closely‐related species in the Rubiaceae family that produce quite different major specialized metabolites including caffeine (a purine alkaloid), camptothecin (anti‐cancer MIAs) and cadambine. This chromosome‐level assembly of N. cadamba genome and analysis of the cadambine synthetic pathway will not only facilitate the development of tools for enhancing bioactive productivity, through metabolic engineering, but will also accelerate our understanding of the evolutionary history of specific metabolic pathways.